Artificial Intelligence in Health Sector of USA - Bimalendu Pendy (CV. Publikasi Indonesia, 2023)
The article describes how AI has already made a significant impact in the health sector in the US, with many promising future applications. In medical imaging, for example, AI algorithms have been developed that can detect and classify anomalies with high accuracy rates, potentially reducing the need for unnecessary biopsies or surgeries. Personalized medicine is another area where AI is being used to analyze large amounts of patient data and provide tailored treatments. AI is also being used to improve the accuracy and efficiency of electronic health records (EHRs) by automatically detecting errors and inconsistencies. In drug discovery, AI algorithms can analyze large data sets and predict which compounds are likely to be effective in treating a particular disease, potentially reducing the time and cost of drug development. In the future, AI is expected to play an even greater role in precision medicine, enabling clinicians to develop customized treatment plans based on a patient's individual genetic and medical history. AI is also being developed for use in virtual assistants, which can provide patients with personalized health advice and reminders. Clinical decision support systems are another area where AI is expected to have a significant impact, helping clinicians to make more informed decisions by analyzing patient data and providing recommendations based on the latest research and best practices. Overall, the article suggests that AI has the potential to transform healthcare by improving patient outcomes, reducing costs, and increasing access to care. However, the article also acknowledges that there are challenges to be addressed, such as ensuring the accuracy and fairness of AI algorithms and addressing privacy concerns.